RNA-binding protein RPS3 contributes to hepatocarcinogenesis by post-transcriptionally up-regulating SIRT1. Issue 4 (4th December 2018) - Zhao, Lijun; Cao, Jianzhong; Hu, Kexin; Wang, Penghui; Li, Guodong; He, Xiaodong; Tong, Tanjun; Han, Limin
Abstract: Although several studies indicate that RNA-binding proteins (RBPs) contribute to key steps in a variety of physiological processes and cancer, the detailed biological functions and mechanisms remain to be determined. By performing bioinformatics analysis using well-established hepatocellular carcinoma (HCC) datasets, we identified a set of HCC progression-associated RBPs (HPARBPs) and found that the global expression of HPARBPs was significantly correlated with patient prognosis. Among the 42 HPARBPs, human ribosomal protein S3 (RPS3) was one of the most abundant genes whose role remains uncharacterized in HCC. Gain- and loss-of-function analyses demonstrated that RPS3 promoted HCC tumorigenesis both in vitro and in vivo . Mechanistically, we revealed that silent information regulator 1 (SIRT1) was a critical target of RPS3 and was essential for sustaining the RPS3-induced malignant phenotypes of HCC cells. RPS3 stabilized SIRT1 mRNA by binding to AUUUA motifs in the 3448–3530 region of the 3′ untranslated region (UTR) of SIRT1 mRNA. In addition, we found that (5-formylfuran-2-yl) methyl 4-hydroxy-2-methylenebutanoate (FMHM) inhibited HCC progression by repressing the RPS3/SIRT1 pathway. Our study unveils a novel extra-ribosomal role of RPS3 in facilitating hepatocarcinogenesis via the post-transcriptional regulation of SIRT1 expression and proposes that the RPS3/SIRT1 pathway serves as a potential therapeutic target in HCC.